Shedding Light Into the Biological Activity of Aminopterin, Via Molecular Structural, Docking, and Molecular Dynamics Analyses - Çelik, Sefa; YILMAZ, GÖZDE; AKYÜZ, SEVİM; Özel, Ayşen E. (Taylor & Francis Inc., 2023)
In this study, the structural and anticancer properties of aminopterin, as well as its antiviral characteristics, were elucidated. The preferred conformations of the title molecule were investigated with semiempirical AM1 method, and the obtained the lowest energy conformer was then optimized by using density functional (DFT/B3LYP) method with 6-311++G(d,p) as basis set. The vibrational frequencies of the optimized structure were calculated by the same level of theory and were compared with the experimental values. The vibrational assignments were performed based on the computed potential energy distribution (PED) of the vibrational modes. The molecular electrostatic potential (MEP) and frontier molecular orbitals (HOMO, LUMO) analyses were carried out for the optimized structure and the chemical reactivity has been scrutinized. To enlighten the biological activity of aminopterin as anticancer and anti-COVID-19 agents, aminopterin was docked into DNA, & alpha;(IIB)& beta;(3) and & alpha;(5)& beta;(1)integrins, human dihydrofolate reductase, main protease (M-pro) of SARS-CoV-2 and SARS-CoV-2/ACE2 complex receptor. The binding mechanisms of aminopterin with the receptors were clarified. The molecular docking results revealed the strong interaction of the aminopterin with DNA (-8.2 kcal/mol), & alpha;(IIB)& beta;(3) and & alpha;(5)& beta;(1) integrins (-9.0 and -10.8 kcal/mol, respectively), human dihydrofolate reductase (-9.7 kcal/mol), M-pro of SARS-CoV-2 (-6.7 kcal/mol), and SARS-CoV-2/ACE2 complex receptor (-8.1 kcal/mol). Moreover, after molecular docking calculations, top-scoring ligand-receptor complexes of the aminopterin with SARS-CoV-2 enzymes (6M03 and 6M0J) were subjected to 50 ns all-atom MD simulations to investigate the ligand-receptor interactions in more detail, and to determine the binding free energies accurately. The predicted results indicate that the aminopterin may significantly inhibit SARS-CoV-2 infection. Thus, in this study, as both anticancer and anti-COVID-19 agents, the versatility of the biological activity of aminopterin was shown.
Keywords: Aminopterin; Densityfunctional Theory; Moleculardocking; Moleculardynamics; FTIR; Raman